Extraction, Identification and Isolation of B-sitosterol from Iraqi Wild Awsaj plant (Lycium barbarum) Using UAE (Probe and Bath) and two isolation technique (HPTLC and PHPLC): B-sitosterol in Iraqi Awsaj plant - abdul-lalil, thukaa zuhair; Hussein, Ahmed Abbas; Saour, Kawkab Y. (Iraqi Journal of Pharmaceutical Sciences, 2017)
Awsaj (Lycium barbarum) is a plant belong to family Solanaceae serves as a good source of bioactive compounds like phytosterols which have many important biological activity. Literature survey available so far revealed that there was no studies about Iraqi wild Awsaj phytosterols especially B-sitosterol, there for the objective of this study was to examine the efficiency of ultrasound assisted extraction (probe and bath) as compared to the conventional (Soxhlet) extraction method for extraction of phytosterols especially B-sitosterol from fruits, leaves, stems and roots of Iraqi wild Awsaj plant. This goal was achieved by comparing the extraction mass yield, also by a quick and easy approach for identification and quantification of bioactive B-sitosterol in four parts of Awsaj using high performance thin layer chromatography (HPTLC) which confirm the presence of B-sitosterol in four parts of Iraqi Awsaj plant and the results clarify that the root part of Iraqi Awsaj plant extracted by probe UAE give the highest concentration (0.610 mg/ml) of B-sitosterol followed by fruits (0.465mg/ml), leaves(0.405mg/ml) and the least was stems(0.275mg/ml); according to these; isolation and purification of B-sitosterol from petroleum ether fraction of Awsaj roots was done by preparative HPLC. The isolated compound (B-sitosterol) was identified by measuring melting point, FT-IR, TLC and preparative HPLC.Key words: Awsaj, ultrasound assisted extraction (UAE), B-sitosterol, high performance thin layer chromatography (HPTLC), preparative high performance liquid chromatography (PHPLC).